KONFLIK TOKOH DALAM NOVEL MALEWA LELAKI YANG BERJALAN DI ATAS AIR KARYA ANDHIKA MAPPASOMBA - Caca Rahma Wati; Sri Suryana Dinar; Asma Wati Ndita; Wa Ode Fitriani Sari (Jurnal Bastra (Bahasa dan Sastra), 2026)
This research is entitled Character Conflict in the Novel Malewa The Man Who Walks on Water by Andhika Mappasomba. The problem of this research is how the character conflict occurs in the novel Malewa Lelaki yang Berjalan di Atas Air by Andhika Mappasomba. This research aims to describe the conflict between the characters in the novel Malewa Lelaki yang Berjalan di Atas Air by Andhika Mappasomba. This type of research is library research, using qualitative descriptive methods. The data in this research is written data in the form of character conflicts in the novel Malewa Lelaki Berjalan di Atas Air by Andhika Mappasomba. The data source in this research is the novel entitled Malewa Lelaki yang Berjalan di Atas Air by Andhika Mappasomba, published by Rumah Bunyi, Kendari, 2019 with a thickness of 143 pages. Data collection techniques in this research are analytical reading, intensive reading and note taking. The data analysis technique used in this research is using a structural approach. The results of this research show that the conflicts contained in the novel Malewa Lelaki Yang Berjalan di Atas Air by Andhika Mappasomba are internal conflict and external conflict. Internal conflict in the novel Malewa Lelaki yang Berjalan di Atas Air by Andhika Mappasomba consists of physical conflict that occurs in the characters Malewa, Cousin Atikah, and Girl Wasior, social conflict that occurs in each character, natural conflict that occurs in the character Malewa, Lelaki Tua, Captain and Crew, and Vice President. The main factor causing conflict in the novel Malewa Lelaki yang Berjalan di Atas Air by Andhika Mappasomba is the conflict between love and parental approval.